Impact of voids on the solder joint integrity and fatigue life of IGBT power module - Sunday E. Nebo; Emeka H. Amalu; David J. Hughes (Power Electronic Devices and Components)
Insulated gate bipolar transistor (IGBT) power module is a key component of actuator devices in many systems which include electric vehicles (EVs). However, as the deployment of IGBT modules penetrates several mission-critical systems operating in harsher ambient, process voids in the solder joints challenge their reliability and fatigue life. This investigation quantifies the impact of presence of 10% voids in critical solder joints on the integrity and fatigue-life of IGBT module for reliable field operation. Computational modelling utilising python programming algorithm deployed in Monte-Carlo technique is used to generate realist distributions of spatial random voids on three representative volume elements (RVEs) of critical solder joints in three IGBT modules. The three modules have elliptical voids, spherical voids and a combination of elliptical and spherical voids, respectively. A fourth control module has no void. Solder joints in the models comprises 96.5% tin, 3.0% silver, and 0.5% copper (SAC305). The IEC 60068-2-14 temperature load cycle and Anand’s visco-plastic model are employed as the load and constitutive model, respectively. Other component materials are modelled with appropriate time and temperature dependent models and material properties. Combined elliptical and spherical voids induced the highest damage while elliptical voids induced the highest plastic strain of 0.045 µm/µm magnitude in the joints. Accumulated stress and strain energy have magnitudes of 74.05 MPa and 2.63 × 105 pJ, respectively. Ten percent elliptical voids in the joints reduced the fatigue life of the module by 59.5%.